Pelatihan Pengolahan Amplang Ikan sebagai Upaya Pemanfaatan Sumber Daya Alam di Gampong Ujong Drien, Aceh Barat - Nabila Ukhty; Ikhsanul Khairi; Akbardiansyah Akbardiansyah; Rosi Rahayu; Rahmawati Rahmawati; Yasrizal Yasrizal (Universitas Teuku Umar, 2024)
Fish cracker production training in Ujong Drien Village, West Aceh Regency, was chosen because the location of the village is along the coast of West Aceh. The absence of small industries or MSMEs in the fish processing sector is proof of the need for this training program. By utilizing the potential of local natural resources, this activity can contribute to the community's economic growth. The aim of this training activity is to equip local communities with knowledge, skills, and motivation, thereby enabling them to develop fish cracker production as a sustainable source of livelihood. This is expected to have a positive impact on the economic welfare of the village. The training process consists of four stages, namely community situation analysis, problem identification, recipe testing, and field implementation. The main results of this program are that participants are able to prepare raw materials and process them according to hygienic standards, participants are able to produce fish crackers according to the correct procedures, and participants are able to produce fish crackers that are tasty and have a crunchy texture.